Integrated Evaluation of Latent Viral Reactivation During Spaceflight - Paloski, W. H.; Pierson, Duane L. (2000)
This application proposes a continuation of our current effort, which has provided the first demonstration of viral reactivation during space flight. We have used the herpesvirus EBV as a model for latent viral reactivation and have shown that increased amounts of EBV DNA were shed by astronauts during space flight. Analysis of the Antarctic space flight analog indicated that the frequency of viral shedding may also increase (along with the increased numbers of virus) during long periods of isolation. However, a number of critical questions remain before the findings may be considered a significant health risk during extended space flight. These include: Are other latent viruses (e.g., other herpesviruses and polyornaviruses) in addition to EBV also reactivated and shed more frequently and/or in higher numbers during space flight? Is the viral reactivation observed in space flight and ground-based analogs mediated through the hypothalamus-pituitary-adrenal (HPA) axis resulting in a decreased cell-mediated immune response? How does detection of viral DNA by PCR analysis correlate with infectious virus? How does the amount of virus found during flight compare with viral levels observed in acute/chronic viral illnesses and in control individuals? This expanded study will examine the phenomenon of viral reactivation from the initiating stress through the HPA axis with the accompanying suppression of the immune system resulting in viral reactivation. This information is essential to determine if latent viral reactivation among crewmembers represents a sufficient medical risk to space travel to require the development of suitable countermeasures.